Applications of scanning ion conductance microscope in biomedical fields. Issue 1 (3rd January 2023) - Gong, Xinrui; Fan, Xinyuan; Huang, Yiming; Du, Yuqi; Wang, Xiaoyu; Liu, Xiaoyu; He, Zhiyao
Abstract: Scanning ion conductance microscopy (SICM) is a scanning probe technique to reflect the surface morphology of the sample with the probe's motion trajectory through measuring the current between the probe and the surface of the sample. Since the surface of the sample can be scanned noncontact and the morphological characteristics of the living cell can be obtained under physiological conditions, SICM is particularly important in the field of biomedicine. SICM has strong potentials in various applications, such as the real‐time and high‐resolution imaging of living cells, monitoring the volume and movements of living cells. In addition, SICM combines with various technologies such as patch clamp and nanopipette to study the physical properties of cells. Furthermore, using SICM to observe cell and tissue structure provides more directions for studying the mechanism of disease. This review briefly introduces the principles and imaging modes of SICM and outlines the recent applications and development of SICM in biomedical research. We also introduce the limitations of the existing SICM technology and make a perspective on its future development. Abstract : Scanning ion conductance microscope has strong potentials in various living biological samples, such as the real‐time and high‐resolution imaging of living cell, monitoring the volume and movements of living cell.